ANALOG COMPUTER FOR STUDYING DIATOMIC MOLECULAR SPECTRA IN TERAHERTZ FREQUENCY - Usman Malik; Muhamad Hamdi; Salomo Salomo (Program Studi Fisika Universitas Negeri Jakarta, 2018)
This paper introduces a harmonic oscillator model for rovibronic terahertz spectrum of a model of a rigid diatomic rotor with some control parameters. The model shows a study of rotationally-resolved terahertz band spectra of the vibrational transition in diatomic molecules. THz radiation absorption is used as a closed-form system known as the analog computer dynamics mode. The optical terahertz region spectrum of the diatomic molecule consists of a series of lines. Their separations are not exactly constant. A diatomic molecule is not truly a rigid rotator, because it simultaneously vibrates with a small amplitude. Due to quantized vibrational and rotational energy levels and the selection rules, allowed transitions result in a highly ordered spectrum consisting of a P branch separated by a central gap. Adjacent spectral lines are separated by a spacing of 2B, and since line intensities depend on Boltzmann factor for thermal population and quantum number J, each branch monotonically increases and decreases. As temperature increases, more lines are observed, and line intensities decrease due to the population being spread over more rotational levels. Interactivity research also involves on effects of the fundamental vibrational frequency, rotational constant B and temperature included line width on the observed spectrum.